Digital Transformation in the Economic Growth of Indonesian Sharia Bank Services - Erna May Wulandari; Maya Indriastuti (Faculty of Economics and Management, 2023)
This study aims to analyze economic growth and digital banking transformation as seen from the Indonesian Islamic banking industry. The development of Islamic finance provides a new perspective on the study of the relationship between economic growth and the transformation of the digital banking industry. Digital banking transformation is an important issue in today's banking industry. The disruption of the digital era has changed the way a person conducts transactions in business. The dynamics of understanding the use of technology in financial literacy is still low so that it can encourage economic growth and improve people's welfare. In addition, there are very few studies on the growth finance nexus that can be viewed from an Islamic finance perspective, especially in Indonesia. The method in this study uses a literature study that is used in writing this article in the form of an assessment of research journals, dissertations, studies, and relevant mass media. This study uses qualitative data and secondary data sources. The implications of this research only focus on Islamic banking, making digital transformation a priority strategy in efforts to increase economic growth in Indonesia. So, this research contributes to the discussion of economic growth that can be influenced by digital transformation in the use of digital services in Islamic banks in Indonesian.